PEMBINAAN KARAKTER PEDULI LINGKUNGAN MELALUI PENGELOLAAN SAMPAH ORGANIK DI SDN PASARKEMIS III KABUPATEN TANGERANG - Galuh Puspita; Ina Magdalena; Ino Budiatman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Environmental care is an important character trait that should be instilled in students from the elementary school level. However, there are still students who lack awareness of maintaining the cleanliness of the school environment, such as disposing of waste improperly and showing little concern for environmental cleanliness. This study aims to describe the development of environmental care character through organic waste management at SDN Pasarkemis III, Tangerang Regency. This research employed a qualitative approach with a descriptive method. The research subjects consisted of the principal, the Adiwiyata teacher, and students. Data were collected through observations, interviews, and document analysis, then analyzed using data reduction, data presentation, and conclusion drawing. The validity of the data was ensured through technique triangulation. The results showed that the development of environmental care character was carried out through various habituation activities, such as the LISA (See Litter, Pick It Up) program, classroom cleaning duties, classroom cleanliness competitions, and organic waste management as part of the Adiwiyata program. Through these activities, students were accustomed to maintaining environmental cleanliness, sorting waste according to its type, and utilizing organic waste based on the 3R (Reduce, Reuse, Recycle) principles. Therefore, organic waste management serves as an effective means of developing students' environmental care character at SDN Pasarkemis III, Tangerang Regency..